RELATIONSHIP BETWEEN NON-PHOTOSYNTHETIC VEGETATION, INTENSITY OF FIRE AND FIRE RADIATIVE POWER IN THE AMAZON - Capanema, Vinicius; de Souza, Greison Moreira; Leite Silva Junior, Celso Henrique (Ra’e Ga: o Espaço Geográfico em Análise, 2021)
Carbon emissions from fires can invalidate efforts to reduce carbon emissions from deforestation This paper aims to present the possible relationship between non-photosynthetic vegetation (NPV), the intensity of burning (dNBR) and fire radiative power (FRP) in southeastern Legal Amazon. For this purpose, two OLI/Landsat 8 images, corresponding to scene 227-068 of 2014, were used to map burn scars in the area. Mapping of burn scars in 2014 resulted in 442.2 km² (2.2% of overall area). It was not observed burned areas in forests fragments located far from agricultural areas, which means that forest fires recurrence occurred on the edges of agricultural areas. The correspondence between NPV with dNBR and FRP was low. The non-use of fire as a management practice in agricultural areas and the use of no-till system justified the weak correlation between the NPV, dNBR and FRP.